2004
DOI: 10.1111/j.1471-8286.2004.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microsatellite markers in a neotropical seasonally dry forest tree, Astronium urundeuva (Anacardiaceae)

Abstract: Nine dinucleotide microsatellites were developed in Astronium urundeuva (Anacardiaceae), a typical tree of the seasonally‐dry tropical forests of South America and characterized on three populations from Paraguay and Argentina. Seven microsatellites were found polymorphic in within population gene diversities ranging from 0.32 to 0.91, and an observed number of alleles varying between four and 20. Despite their relatively low number of alleles, these markers proved valuable tools in detecting genetic structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Geoffroea spinosa has vertebrate dispersed fruits, and is found distributed in nearly all the areas described above. As part of a program aiming at analysing the postglacial distribution of NSDF typical species, microsatellites have been developed in this species, together with another characteristic NSDF species, Astronium urundeuva (Caetano et al . 2005).…”
Section: Characteristics Of 11 Optimized Microsatellites In Geoffroeamentioning
confidence: 99%
See 1 more Smart Citation
“…Geoffroea spinosa has vertebrate dispersed fruits, and is found distributed in nearly all the areas described above. As part of a program aiming at analysing the postglacial distribution of NSDF typical species, microsatellites have been developed in this species, together with another characteristic NSDF species, Astronium urundeuva (Caetano et al . 2005).…”
Section: Characteristics Of 11 Optimized Microsatellites In Geoffroeamentioning
confidence: 99%
“…These 10 polymorphic loci should be useful for the study of G. spinosa genetic structure, and should give us insights into the past history of NSDF together with the study of other species (e.g. Astronium urundeuva , Caetano et al . (2005)).…”
Section: Characteristics Of 11 Optimized Microsatellites In Geoffroeamentioning
confidence: 99%
“…The use of molecular markers in population genetic studies of tree species has been shown to be effective. In M. urundeuva, previous studies were performed using isoenzyme markers [7,8], RAPD and cpDNA [9,10], AFLP [11,12] and more recently by microsatellite markers [1,3,[13][14][15]. In these last studies, nine microsatellite loci developed by Caetano et al [13] were used in the analysis of populations of M. urundeuva only from Paraguay and Argentina.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction amplification of SSR loci were conducted to evaluate five loci described for M. urundeuva in Caetano et al (2005). Thus, the PCRs were composed of 1 ng of genomic DNA in a final volume of 6 mL containing: 200 µM of each dNTP, 2.5 mM MgCl 2 , 0.33 mM of each primer, ultrapure sterile water and 1x Go Taq Master Mix PROMEGA.…”
Section: Methodsmentioning
confidence: 99%